Generating Employment opportunity for the extreme poor during Monga - Naser, Mohammad Anwarul (Institute of Governance Studies, BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2009.